A Simulator Program for Evaluating and Improving the Nottingham Muse Architecture. - Barrett, Neil K.; Brailsford, David F.; Duckworth, R. James (Computer Science, 1986)
This paper describes the modelling and simulation of the Nottingham MUSE (MUltiple Stream Evaluator) machine. MUSE is a data flow machine capable of supporting structured parallel computation. The simulator described in this paper was designed to enable alterations, improvements and additions to be made to the prototype MUSE architecture. The stages through which the model has progressed, and the implementation details of this model as a program, are discussed. The validation experiments are explained, and future plans for alterations and modifications to the basic model are suggested.